2012
DOI: 10.1103/physrevlett.109.105703
|View full text |Cite
|
Sign up to set email alerts
|

Avalanches in Strained Amorphous Solids: Does Inertia Destroy Critical Behavior?

Abstract: Simulations are used to determine the effect of inertia on athermal shear of amorphous two-dimensional solids. In the quasistatic limit, shear occurs through a series of rapid avalanches. The distribution of avalanches is analyzed using finite-size scaling with thousands to millions of disks. Inertia takes the system to a new underdamped universality class rather than driving the system away from criticality as previously thought. Scaling exponents are determined for the underdamped and overdamped limits and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
182
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(206 citation statements)
references
References 38 publications
20
182
4
Order By: Relevance
“…21 where the critical scaling of avalanches in quasistatic shear of disordered systems is discussed . They showed that Γ c = 0.1 (τ = 10) is a critical damping rate separating the overdamped (larger Γ) and underdamped (smaller Γ) regimes which are characterized by different scaling behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 where the critical scaling of avalanches in quasistatic shear of disordered systems is discussed . They showed that Γ c = 0.1 (τ = 10) is a critical damping rate separating the overdamped (larger Γ) and underdamped (smaller Γ) regimes which are characterized by different scaling behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate how inertia affects the response, different conditions of the underlying dynamics, from overdamped to underdamped, are considered. This is motivated by recent work by Salerno et al [21] where the role of inertia on the critical behavior of avalanches in strained amorphous solids is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between these two phenomena has led to the proposition that the yielding transition is in the universality class of mean-field depinning (33, 34). However, experiments find a reological exponent β > 1 against the β ≤ 1 predicted for elastic depinning, and numerical simulations display intriguing finite size effects that differ from depinning (9,10,(35)(36)(37).Formally, elasto-plastic models are very similar to automaton models known to capture the depinning transition well (17); the key difference lies in the interaction kernel G, long-ranged and of variable sign for elasto-plastic models while essentially a Laplacian for depinning with short-range elasticity. We recently showed (20) that in the presence of long-ranged interaction with variable sign, the distribution of shear transformations at a distance x from instability, P(x), is singular with P(x) ∼ x θ , unlike in depinning for which θ = 0.…”
mentioning
confidence: 99%
“…The comparison between these two phenomena has led to the proposition that the yielding transition is in the universality class of mean-field depinning (33, 34). However, experiments find a reological exponent β > 1 against the β ≤ 1 predicted for elastic depinning, and numerical simulations display intriguing finite size effects that differ from depinning (9,10,(35)(36)(37).…”
mentioning
confidence: 99%
“…[15,20] showed that disordered solids undergoing underdamped dynamics enter a nontrivial universality class, where τ appears to show a crossover from ∼ 1.3 to ∼ 1.6 when it is estimated through the stress drops. This exponent crossover together with the qualitative features (hump) of the universal scaling function and the steady-state average stress consistent decrease, all resemble the behavior of our model.…”
Section: Consistency With Microscopic Molecular Dynamics Simulationsmentioning
confidence: 99%